Constructing collaborative learning communities of teachers: a case study in Portugal - Silva, Ana Maria Costa e (2019)
The work and collaborative learning of teachers are recognized, as fundamental factors in the professional development of teachers and in the quality of educational organizations. This text presents some results of a case study carried out in a Group of Schools in the north of Portugal staffed by 134 teachers of various educational levels by means of a qualitative and quantitative methodology. The objectives of the investigation focused on understanding the way that the teachers described their learning opportunities, recognized the facilitating and inhibiting elements of collaborative professional learning in the workplace and analyzed the way how the teachers perceived their professional learning in the work place. Information was collected by recourse to an enquiry using a questionnaire and semi-structured interviews. Fundamentally we focused on results of a qualitative nature with particular attention to information resulting from the interviews and also from the questionnaires. The results showed the recognition on the part of the teachers of the ways and contexts of collaborative work and learning and their importance in their professional daily life and quality of work. They also reflected that, although the teachers recognized these contexts in their current professional experience, they did not associate these experiences directly to communities of practice.